Developing Fashion Design Vocational Career Guidance Module - Karend, Khanza Azizah Abas; Sutopo, Yeri; Widjanarko, Dwi (Journal of Vocational and Career Education, 2020)
This research was conducted with the main problem, namely the lack of resources that can be used by productive teachers in Vocational High Schools (SMK) in supporting industrial career path learning. Teaching materials that can be used as a provision to prepare students to enter the workplace, especially the fashion study program. This research aims to produce a feasible, practical, and effective module. In this research method, the R&D, the chosen design is ADDIE which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The unit of analysis of this research is the fashion design vocational career guidance module. The instruments used in this study are (1) module assessment sheets; (2) questionnaires; and (3) and a questionnaire. The data analysis used in this study consisted of: (1) categories to determine the feasibility level of the module; (2) Guttman's categorization for the practicality of the module, using the coefficients Kr and Ks; and (3) n gain test using t test, for module effectiveness. The results of the module feasibility test obtained a score of 4,71% with a very feasible category, the practicality of the module is 88% with very practical criteria, and the effectiveness of the module obtained an N-Gain score of 82.37%. It can be concluded that the module is effectively used as vocational teaching materials. Previous research is developing a printed career material module in a broad scope and it is necessary to have a career focus in a particular field. In this study, the module focuses on a career in fashion that is feasible, practical, and effectively used by productive students and teachers in learning industrial career paths.